Customary Shift Based on Islamic Teachings, Ban on Music in Naumbai Village, Kampar, Riau; Ethnographic Study - Zulkifli; Amrizal; Zein, Nurhayati; Rahima Munawarah Raja Ahmad, Raja (Universitas Pendidikan Ganesha, 2024)
Customary traditions represent a cultural identity inherited across generations, playing a crucial role in preserving social harmony within communities. However, the rapid flow of globalization and modernization has driven a shift in the meaning of customs, threatening their philosophical values and existence. This study aims to analyze the historical dynamics, forms of meaning shifts, and implications of the baoguong (music prohibition) tradition on community behavior patterns. Employing a qualitative ethnographic approach, the research involved 13 purposively selected informants. Data were collected through in-depth interviews, participant observations, and field notes, using an instrument framework based on William F. Ogburn's (1992) theory of social change. Data were analyzed using Spradley’s ethnographic analysis technique. The findings reveal that the baoguong prohibition originated from a religious teaching by Haji Ahmad in 1901, initially carrying an associative-religious meaning which later shifted to a lexical interpretation during the era of Muhammad Yatim (1965). This shift impacted the younger generation, who continued musical activities through modern media such as tape recorders and smartphones. The transformation of the material elements of the tradition has caused changes in its immaterial elements, notably in its religious and social meanings. This study recommends revitalizing traditional values through adaptive educational strategies that align with the contemporary socio-cultural context.